Effect of Grammar Racing Game on Learning Simple Present Tense to Improve Achievement of Elementary Education Students at Palangka Raya University - Muhammad Rezeki (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study is aim to find out the significant effect of using grammar racing game to the students’ grammar score (simple present tense)  and the students’ interest toward grammar racing as media in teaching grammar for the Students of Elementary School Education Teacher Program In University of Palangka Raya. The study includes in Quantitative Paradigm with Experimental Design. The researcher designed the Lesson Plan, conducted the treatment and observed the students’ score by pretest and posttest. The population of study was at the first semester students which consisted of three classes. The researcher chose 1A as sample. The sample was determined using purposive sampling technique. After getting the data that were from pretest and posttest, the researcher analyzed the data using ttest formula to test the hypothesis stated based on the result of analysis, it was found that the value of tobserved = 8.677 and the ttable =2.03. It showed that the tobserved was higher than the ttable and to answer the second alternative hypotheses research used questionnaire there are 94 % of 43 students of 1A was interest toward grammar racing game as media in teaching grammar. The result of testing hypothesis determined that the Alternative Hypothesis (Ha) stating that there was significant effect of using grammar racing game toward student’s grammar score of Elementary School Education Teacher Program was accepted and Ho stating that there was no significant effect of using grammar racing toward student’s grammar score was rejected.